Advancing Women in Science, Medicine and Global Health: On the #Lancetwomen Special Issue [Liderazgo de Las Mujeres en Ciencia, Medicina y Salud Global: Comentando el Número Especial #Lancetwomen] - Bachelet-Norelli, V (Medwave Estudios Ltda, 2019)
[No abstract available]